Catalyst-free hydroboration of CO2 with a nucleophilic diborane(4) - Frick, Markus; Wadepohl, Hubert; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2018)
Hydroboration generally requires the presence of a catalyst to lower the barrier for hydride transfer. This work reports on the first catalyst-free CO2 hydroboration with a neutral boron compound, the nucleophilic diborane [HB(hpp)]2, 1 (hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate). Further hydroboration reactions to bis(boryl)acetals are possible. In acetonitrile, but not in dichloromethane solutions, hydroboration of a first CO2 is followed by hydroboration of a second CO2 molecule. Detailed kinetic measurements for both hydroboration steps were carried out and the influence of the solvent and the addition of a Lewis base on the rate constants analyzed. In contrast to catalyst-free hydroboration of CO2, hydroboration of the less electrophilic acetone requires the presence of an activating Lewis acid.
Im Titel ist „2“ tiefgestellt
Gesehen am 24.07.2019